Are Village Fund and Village-Owned Enterprises Crucial in Eradicating Poverty in Indonesia - Azhari Azhari; Muhammad Yusuf; Kamaruddin Kamaruddin; F. Fadly (Jurnal Ekonomi dan Bisnis Jagaditha, 2022)
This study aims to examine the village funds and village-owned enterprises in reducing poverty in Indonesia. The village fund has been rolled out since 2015 by the government of the Republic of Indonesia. The data used is panel data by combining time series data and panel data from 2015 to 2021. The population of this study consists of all villages in 23 districts/cities in Aceh propince, with the total of 6.497 villages, using panel regression as an analytical tool. The result of this study showed that although village funds and village-owned enterprises do have effect in reducing the number of poor people in rural areas, however, the impact of village fund is more significant compared to village-owned enterprises. In this case relevant stakeholders should be able to increase the capacity of village fund managers through internship programs, mentoring and capacity building for managers. Multi-stakeholder cooperation is highly recommended in empowering village-owned enterprises as a source of village original income. The limitation of this study is it does not distinguish the type of business from each existing business owned by the village. Therefore, the future research needs to evaluate the type of business in a village-owned enterprise.